2016
DOI: 10.1007/s11128-016-1461-2
|View full text |Cite
|
Sign up to set email alerts
|

New quantum dialogue protocol based on continuous-variable two-mode squeezed vacuum states

Abstract: A new quantum dialogue protocol is designed by using the continuousvariable two-mode squeezed vacuum states due to its entanglement property. The two communication parties encode their own secret information into the entangled optical modes with the translation operations. Each communication party could deduce the secret information of their counterparts with the help of his or her secret information and the Bell-basis measurement results. The security of the proposed quantum dialogue protocol is guaranteed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…We found that access to small quantum memory (a qubit) does not help the eavesdropper to attack the SDIQKD protocol and conjecture that the same holds for other protocols and unlimited memory. As QKD in general is gaining immense popularity [25,26,27,28] and entanglement based QKD remains commercially nonviable, devices employing prepare and measure QKD schemes seems to be η critical avg (a) (b) (2 → 1) QRAC 0.71 1 2 (3 → 1) QRAC 0.58 1 3 natural way forward. Our analysis other than being robust, deals with worst case scenarios and provides for the everyday naive user a hassle-free way to infer about the security his devices offer.…”
Section: Discussionmentioning
confidence: 99%
“…We found that access to small quantum memory (a qubit) does not help the eavesdropper to attack the SDIQKD protocol and conjecture that the same holds for other protocols and unlimited memory. As QKD in general is gaining immense popularity [25,26,27,28] and entanglement based QKD remains commercially nonviable, devices employing prepare and measure QKD schemes seems to be η critical avg (a) (b) (2 → 1) QRAC 0.71 1 2 (3 → 1) QRAC 0.58 1 3 natural way forward. Our analysis other than being robust, deals with worst case scenarios and provides for the everyday naive user a hassle-free way to infer about the security his devices offer.…”
Section: Discussionmentioning
confidence: 99%
“…36 is a one-and two-mode combined squeezed vacuum state. The one-mode squeezing corresponds to quadratic operators in the exponent such asb 2 2 , and the two-mode squeezing to the products of different operators such asb 1b2 .Being generalizations of the generic squeezed vacuum, the optical output states can be used for the implementations of quantum teleportation [26], quantum metrology [30], quantum dense coding [32], quantum dialogues [33] and electromagnetically induced transparency protocols [38]. Squeezed vacuum states have non-vanishing intensities, and since a beam splitter under CPA conditions emits squeezed vacuum states of light, coherent perfect absorption of intensity is not possible, and A I sq < 1 for non-vanishing squeezing.…”
Section: Continuous-variable Quantum State Preparation With Cpamentioning
confidence: 99%
“…Internet of Things (IoT) facilitates data getting and sending for all sensors/devices through the transmission network [39][40][41][42][43][44][45][46][47]. The cloud part of the IoT result facilitates data preprocessing and filtering previous to affecting it to the cloud and broadcasts control instructions from the cloud to objects [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%